Analysis of Spanish policies for the integration of immigrant schoolchildren. Issue 3 (3rd May 2016) - Martínez-Usarralde, María Jesús; Yanes-Cabrera, Cristina; Llevot-Calvet, Nuria
Abstract : The Organic Law on the Improvement of the National Education Quality ( Ley Orgánica de Reforma de la Calidad Educativa ) readdressed one of the most significant educational issues: educational policies related to immigrant students. Therefore, this is an appropriate moment to evaluate these types of policies in three singular Spanish regions: Madrid, Catalonia and Andalusia. This article presents an analysis of the measures taken in three Spanish regions: Madrid, Catalonia and Andalusia in response to students' reception, acceptance and enrolment of immigrant students. A qualitative methodology based on the comparative method is used. Diverse similarities, but also specific characteristics and differences, can be found among the three models associated with each region. There are several significant differences that can be appreciated, such as the institutional role, as well as other specific measures. However, singular features are also identified, such as the diverse policies for the use of the vehicular language in each of the cases. Finally, the comparisons highlight various critical aspects, such as attention devoted to the students' native language and progress towards intercultural education in school strategies and planning.